Stroke and atrial septal defects – decision making at the turning of ages - Vlad Eugen Tiu; Athena Ribigan; Raluca Badea; Ovidiu Bajenaru (Romanian Journal of Neurology, 2017)
CLOSE and Gore-REDUCE trials have recently changed the way we approach patients with stroke and patent foramen ovale. We present the case of a young patient with an Embolic Stroke of Undetermined Source (ESUS) and an atrial septal defect causing a large right-to-left shunt, with an ample discussion on evidence-based decision making.